Analisis Kinerja Keuangan BCA Dibandingkan Dengan Industri Perbankan Di Bursa Efek Indonesia - Aini, Yulia Nurul; Darmayanti, Ni Putu Ayu (E-Jurnal Manajemen; Vol 3 No 6 (2014), 2014)
This study was conducted to determine the significance of differences in the financial performance and position of the Bank BCA's financial performance compared to the banking industry in Indonesia Stock Exchange . The population is banking companies listed in Indonesia Stock Exchange 2009-2012 . Based on the results of the study found that there are significant differences in the average financial performance when viewed from the ratio of profitability and liquidity ratios , and there is no significant difference in the average performance when seen from the financial leverage ratio , market valuation ratio , and the ratio between the activity of BCA with industry banking in Indonesia Stock Exchange 2009-2012 . The position of the Bank 's financial performance compared to the banking industry in the period 2009-2012 Indonesia Stock Exchange seen from BCA profitability ratios higher than the banking industry in Indonesia Stock Exchange . Meanwhile , in terms of liquidity ratios , leverage ratios , the ratio of market valuation and BCA activity ratio lower than the banking industry in Indonesia Stock Exchange Keywords : financial performance, ratio analysis